2009
DOI: 10.1016/j.healthplace.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the experience of place: Expanding methods to conceptualize and measure community integration of persons with serious mental illness

Abstract: Community integration research explores community contexts and factors that encourage or hinder individuals with serious mental illness (SMI) from actively participating in community life. This research agenda can be advanced by using mixed-methods that better document the relationships between contextual factors and individual experience. Two such methods were applied to a mixedmethods study of 40 adults with SMI living in independent housing in the Southeastern United States. Their contextualized experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
59
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 45 publications
4
59
0
3
Order By: Relevance
“…For these participants, small activity spaces reflected social ties within a local geographic area, consistent with results from previous studies where people with smaller activity spaces were shown to experience a stronger sense of community. 5 However, there were contrasting results for two other participants in this activity space size measure (<5 km). Despite occupying a local geographical area, these participants had minimal social ties or meaningful places nearby (ID 19).…”
Section: Patterns In Activity Spaces: Understanding Presence In the Cmentioning
confidence: 75%
See 4 more Smart Citations
“…For these participants, small activity spaces reflected social ties within a local geographic area, consistent with results from previous studies where people with smaller activity spaces were shown to experience a stronger sense of community. 5 However, there were contrasting results for two other participants in this activity space size measure (<5 km). Despite occupying a local geographical area, these participants had minimal social ties or meaningful places nearby (ID 19).…”
Section: Patterns In Activity Spaces: Understanding Presence In the Cmentioning
confidence: 75%
“…1 Community and community participation (CP) in turn involve social and emotional connections constructed in physical spaces, movement across spaces, and the qualities of spaces. [2][3][4][5][6] These connections are dynamic over time -shifting with considerations such as self-concept, socio-economic context and culture. 7 In mental health literatures, community is framed as a resource (social and otherwise) -a place where recovery most readily occurs; and participating in communities is an often-cited treatment, service and system objective.…”
mentioning
confidence: 99%
See 3 more Smart Citations